Decision Maker's Tool: Statistics, the Problem Solver - Faith Cajudo Orillaza (Westcliff University, 2018)
The primary objective of every investor is to see how his money grows. No matter where one decides to plant or invest his money, there is an inevitable process that follows. The important thing is to closely monitor events and record every detail of information. Unless there is a proper system, issues will build and may become difficult to manage. This is the main reason why there are tools which are necessary to use when planting the seeds for investments. These tools are packed into one parcel and referred to as statistics. The term statistics will refer to descriptive and inferential statistics, probability, parametric and non-parametric tests, time series, and business intelligence. This paper will define statistical gears which are normally used by business managers to gather and analyze data for planning and decision-making. It will further highlight how the elements of statistics can build a strong pillar to run a business and alleviate potential challenges through the use of a tool known as the problem solver.